2017
DOI: 10.1007/s13187-017-1168-9
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Screening and Social Media: a Content Analysis of Evidence Use and Guideline Opinions on Twitter

Abstract: There is ongoing debate regarding the best mammography screening practices. Twitter has become a powerful tool for disseminating medical news and fostering healthcare conversations; however, little work has been done examining these conversations in the context of how users are sharing evidence and discussing current guidelines for breast cancer screening. To characterize the Twitter conversation on mammography and assess the quality of evidence used as well as opinions regarding current screening guidelines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 18 publications
1
35
0
4
Order By: Relevance
“…As stated by Nastasi, A., Bryant, T., Canner, J. K., et al (2017) in their own Twitter study, "Non-healthcare users comprise a significant proportion of participants in mammography conversations, with tweets often containing claims that are false, not explicitly backed by scientific evidence, and in favor of alternative "natural" breast cancer prevention and treatment." [27].…”
Section: The Content Of Discoursementioning
confidence: 99%
See 3 more Smart Citations
“…As stated by Nastasi, A., Bryant, T., Canner, J. K., et al (2017) in their own Twitter study, "Non-healthcare users comprise a significant proportion of participants in mammography conversations, with tweets often containing claims that are false, not explicitly backed by scientific evidence, and in favor of alternative "natural" breast cancer prevention and treatment." [27].…”
Section: The Content Of Discoursementioning
confidence: 99%
“…[24][25][26] The online presence of scientifically unfounded and misleading breast cancer screening information (mammography causes breast cancer, breast cancer can be prevented by organic food) is evidenced by other studies, too. [27] Nastasi, A., Bryant, T., Canner, J. K., Dredze, M., Camp, M. S., Nagarajan, N. (2018) found that only 61% of the 323 tweets posted by lay people had scientific support. The scientifically false tweets are liked and shared as often as the reliable ones in this study.…”
Section: The Content Of Discoursementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the qualitative and quantitative relevance of tweets has been shown in various investigations, including analyses of the interests and feelings of the general population with respect to health/disease, the interactions between patients and doctors/health providers and the generation of the scientific impact of medical research in the news media. Furthermore, patient attitudes toward various medical topics, including vaccines, illnesses, pain, drug use, and both oncological and cardiovascular disease, have been analyzed [23][24][25][26][27][28][29][30][31]. Consequently, the analysis of distributed tweets by primary social media channels on mental health disease and the frequency of retweets generated may be effective tools for assessing social and individual interest toward psychiatric diseases.…”
Section: Introductionmentioning
confidence: 99%